HUMANS AS PEDAGOGIC CREATURES: Islamic and Western View - D, Muh. Akib; Idris, Ridwan (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: The essence of human creation in Islamic perspective refers to the text of the Koran in terms of khalaqa (creating) and ja’ala (making). Both elements can grow through the educational process. This perspective points that humans are naturally pedagogical beings with the potential for education. This paper aims at elaborating the essence of humans as pedagogic creatures, both in Islamic and Western views. This study relied on library research for its findings. The information was gathered from a variety of books and papers on the subject. In the Islamic view, the level of education development, along with the pedagogical process that initiates it, involves informal, formal, and non-formal education. However, in the Western view, there are two categories, namely navitism and behaviorism. Abstrak: Hakekat penciptaan manusia dalam perspektif Islam dengan merujuk pada nash Alquran pada istilah khalaqa (menciptakan) dan ja’ala (menjadikan). Kedua unsur itu dapat berkembang melalui proses pendidikan. Perspektif ini menyatakan bahwa manusia secara fithrawi disebut sebagai makhluk paedagogiek dengan potensi untuk dapat dididik dan dapat mendidik. Artikel ini bertujuan untuk memaparkan hakekat penciptaan manusia sebagai makhluk paedagogiek, baik dalam pandangan Islam maupun Barat. Penelitian ini menggunakan penelitian kepustakaan. Data pada penelitian ini diambil dari berbagai buku dan artikel yang berkaitan dengan topik tersebut. Dalam pandangan Islam, tingkat perkembangan pendidikan manusia, seiring dengan proses paedagogis yang mengintarinya meliputi pendidikan informal, formal, dan non formal. Sedangkan dalam pandangan Barat, ditemukan dua kategori yaitu paham navitisme dan paham behaviorisme.